The Intergenerational Transmission Effect of Depression: Causality, Resilience & Decomposition - Mthembu, Simeme (School of Economics, 2023)
Since the 1990s, the burden of disease associated with poor mental health has continued to rise in South Africa. One third of South Africans will suffer from poor mental health in their lifetime if either parent also suffers from poor mental health, and this intergenerational transmission effect of depression is large and highly significant. Previous work has attempted to investigate whether it is nurture or nature effects which drive this large transmission effect. While this work has found that it is primarily environmental factors which account for this transmission of depression from mother to child, this does not properly identify the extent of each component, and in which contexts the one is more important than the other. Despite the prevalence of poor mental health, the intergenerational transmission of mental illness in South Africa is equally understudied. Investigating whether this intergenerational transmission of depression is a causal effect or merely a correlation poses a major challenge for inference. This thesis estimates causality in the intergenerational transmission effect of depression from parent to individual, and finds that parental depression is the the single largest determinant of individual depression. That is, individuals with depressed parents are more likely to suffer from depression themselves. This thesis also attempts to explore vulnerability and resilience to this transmission effect and finds that a mother's depression is the largest and most important determinant of transmission of depression from a father. The opposite is also true - a father's depression is the single and largest determinant of transmission of depression from a mother. Upon further investigation of the key determinants of resilience or vulnerability to transmission using the Least Absolute Shrinkage and Selection Operator (lasso) model, this paper finds that hardly any other genetic or environmental characteristics have been found to be significant determinants of transmission. Parental depression alone has the largest effect on whether an individual is resilient or vulnerable to transmission from another parent. This paper finds that the environment does not seem to have as large of an effect on resilience or vulnerability to transmission of depression as was previously thought in the literature - only parental depression seems to have an effect on transmission of depression.